Influence of Inorganic Inhibitors on the Strength and Corrosion Resistive Properties of Quarry Dust Concrete - Devi, M.; Kannan, K. (Asian Journal of Chemistry, 2011)
Demand of quarry dust for making concrete is increasing day by day because availability of natural sand is getting depleted and it is becoming costly. This paper deals with an experimental study undertaken to investigate the use of quarry dust as fine aggregate in concrete. Experimental work has been carried out with calcium nitrite, calcium nitrate and sodium nitrate as corrosion inhibitors at the dosage of 1, 2, 3 and 4 % by weight of cement. The effectiveness of these inorganic inhibitors was studied using various electrochemical techniques such as rapid chloride penetration test (RCPT), accelerated corrosion test, A.C. impedance measurement and gravimetric weight loss measurement. The mechanical properties such as compressive strength, flexural strength, spilt tensile strength and bond strength in addition to water absorption were also studied and the optimum percentage addition of each inhibitor was determined. Results herein revealed that replacement of sand by quarry dust increases the strength of the concrete; with addition of inhibitor it offers lower permeability and greater density which enable it to provide better resistance to corrosion and durability in adverse environment.